Renovations of neighbourhood parks: long-term outcomes on physical activity. Issue 3 (3rd January 2019) - Cohen, Deborah A; Han, Bing; Isacoff, Jennifer; Shulaker, Bianca; Williamson, Stephanie
Abstract : Background: Neighbourhood parks are places designed to support physical activity, but are often underutilised. Park renovations are major improvements to the quality of these spaces and usually attract more park users. This study assessed changes in the use of six San Francisco neighbourhood parks and park-based physical activity levels over a 6-year period, during which five of the six parks were renovated. Methods: We used direct observation to assess park-based physical activity. We used a stepped-wedge study design at three time points in all six parks over 6 years (before all parks were renovated, after two parks were renovated and after an additional three were renovated) to evaluate the short-term and long-term effects of park renovations. Results: Levels of moderate-to-vigorous physical activity (MVPA) and metabolic equivalent hours expended in the parks increased overall, most immediately after renovation. Age groups responded differently with the largest increases in park use and MVPA among adults and children under age 12, with no changes among teens and seniors. Conclusions: Park renovations attracted more users and increased park-based MVPA than non-renovated parks and sustained increases over time for adults and children, but not teens or seniors. Park renovations that consider and provide facilities that support varied levels of physical activity and cater to all age groups may foster increased park-based physical activity that can be sustained.